Folate intake, alcohol consumption, and the methylenetetrahydrofolate reductase (MTHFR) C677T gene polymorphism: influence on prostate cancer risk and interactions - Lindsay C Kobayashi; Lindsay C Kobayashi; Heather eLimburg; Qun eMiao; Qun eMiao; Christy eWoolcott; Leanne L Bedard; Thomas E Massey; Kristan J Aronson; Kristan J Aronson (Frontiers in Oncology, 2012)
Purpose: Folate is essential to DNA methylation and synthesis and may have a complex dualistic role in prostate cancer. Alcohol use may increase risk and epigenetic factors may interact with lifestyle exposures. We aimed to characterize the independent and joint effects of folate intake, alcohol consumption, and the MTHFR C677T gene polymorphism on prostate cancer risk, while accounting for intakes of vitamins B2, B6, B12, methionine, total energy, and confounders.Methods: A case-control study was conducted at Kingston General Hospital of 80 incident primary prostate cancer cases and 334 urology clinic controls, all with normal age-specific PSA levels (to exclude latent prostate cancers). Participants completed a questionnaire on folate and alcohol intakes and potential confounders prior to knowledge of diagnosis, eliminating recall bias, and blood was drawn for MTHFR genotyping. Joint effects of exposures were assessed using unconditional logistic regression and significance of multiplicative and additive interactions using general linear models.Results: Folate, vitamins B2, B6, B12, methionine, and the CT and TT genotypes were not associated with prostate cancer risk. The highest tertile of lifetime alcohol consumption was associated with increased risk (OR=2.08; 95% CI: 1.12-3.86). Consumption of >5 alcoholic drinks/week was associated with increased prostate cancer risk among men with low folate intake (OR=2.38; 95% CI: 1.01-5.57) and higher risk among those with the CC MTHFR genotype (OR=4.43; 95% CI: 1.15-17.05). Increased risk was also apparent for weekly alcohol consumption when accounting for the multiplicative interaction between folate intake and MTHFR C677T genotype (OR=3.22; 95% CI: 1.36-7.59).Conclusion: Alcohol consumption is associated with increased prostate cancer risk, and this association is stronger among men with low folate intake, with the CC MTHFR genotype, and when accounting for the joint effect of folate intake and MTHFR C677T genotype.